Analysis Of The Causes Of Unachieved Realization Of Potential Revenue Bogor City ASN Professional Zakat (Case Study Of The Amil Zakat Agency Of Bogor City) - Sulaeman, Cece; Ayuniyyah, Qurroh; Juwaeni, Ahmad (UNIVERSITAS PAKUAN, 2023)
Zakat is the third pillar of Islam for Muslims who have tremendous potential to implement community economic activities, especially for the poor. Zakat is also an instrument of income distribution that plays a role in the development of the welfare of the people. One of the zakat that we often hear is professional zakat or income zakat. professional zakat of ASN Bogor City has great potential, but the realization professional zakat of ASN Bogor City collection carried out by BAZNAS Bogor City has not been maximized. This study aims to analyze what is the cause of the non-achievement of revenue realization of the potential zakat of the ASN profession in the City of Bogor and what strategies are used to increase the acceptance of zakat for the profession of ASN in the City of Bogor. This research uses a qualitative methodology with a case study approach. The data sources used are primary data sources, data taken directly from informants consisting of BAZNAS Bogor City administrators, Bogor City Regional Government and ASN Bogor City. Data collection techniques were carried out by means of observation, direct interviews with the Bogor City Amil Zakat Agency as zakat manager, Bogor City Government as regulator and ASN Bogor City as muzakki. Secondary data sources are obtained from literature and documentation that support this discussion, such as books, papers, articles and so on. The results of this study conclude that the cause of the failure to achieve the realization of the potential for professional zakat receipts for ASN Bogor City is that there are several government agencies that have the largest potential for professional zakat but do not carry out the mandate of Bogor Mayor Regulation Number 118 of 2020, the low trust of ASN Bogor City towards BAZNAS Bogor City and what strategy will be carried out by the BAZNAS Bogor City to increase the collection of professional zakat funds for the Bogor City ASN profession.